2016
DOI: 10.3329/ajmbr.v1i3.26475
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Human Immunodeficiency virus, Hepatitis B virus, Hepatitis C virus and Syphilis infections among nonprofessional blood donors in Chittagong, Bangladesh

Abstract: Human Immunodeficiency virus (HIV), Hepatitis B virus (HBV), Hepatitis C virus (HCV) andSyphilis infection are the major public health problem, alarming the most developing countries like Bangladesh. These studies determined the prevalence rate and risk factors of HIV, Hepatitis B, Hepatitis C and Syphilis among nonprofessional blood donors in multiple blood transfusion center of Chittagong. Information was collected by questionnaire to find out the relationship of HIV, HBV, HCV and Syphilis infection with age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In this study prevalence rate of HIV was found 1.2%. In previous studies prevalence of HIV among nonprofessional blood donors was found to be 0% in both Dhaka 19 and Chittagong city 10 . But a recent study demonstrated 10% increase in the number of new HIV infections each year [20][21] , which explains the high prevalence rate in our study.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In this study prevalence rate of HIV was found 1.2%. In previous studies prevalence of HIV among nonprofessional blood donors was found to be 0% in both Dhaka 19 and Chittagong city 10 . But a recent study demonstrated 10% increase in the number of new HIV infections each year [20][21] , which explains the high prevalence rate in our study.…”
Section: Discussionmentioning
confidence: 87%
“…All the infected individuals were male donors, 75% were service holder and 25% were from other professions. Whereas, in Chittagong, prevalence of HCV was 0.92% and 100% of positive individual (5.71% of blood donors) were businessman and about 50 % positive donors had an intravenous drug reception history 10,23 . Another study reported that 1.2% professional blood donors were positive for HCV 27 , anti-HCV was found to be positive in 7.3% among the blood donors in Gourgia 28 , 4.16% among the blood donors in Pakistan 29 , and 0.285% 30 among the replacement blood donors in the Western India 10 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Darker hues of red indicate increasing male:female ratio in the study population (blue bars indicate no gender data was available). The percentage of males in the study population range from 81% [33] to 98% (2011 data in [29]). The upshot of this discussion is that despite the existence of a substantial body of literature on Hepatitis B prevalence in otherwise healthy individuals in Bangladesh, most of their sampling frames do not represent the population at large.…”
Section: The Problem Of Representationmentioning
confidence: 99%